Orientalism as a Cultural Root of Western Islamophobia - Badrane Benlahcene (Journal of Islamic Thought and Civilization, 2021)
This paper focuses on Islamophobia as a phenomenon in the western context in order to understand its cultural roots that produce such a stereotype about Islam and the Muslims. It aims to discover these roots relying on the analysis of a sample of intellectual texts expressing the western biases and the concept of western supremacy over Islam, the Muslims and the Islamic civilization, which are contradictory to historical evidence. Therefore, it focuses on the expansion of the western civilization all over the world and its use of orientalism as a justifying tool which consequently formed the underlying foundation of Islamophobia. The paper seeks to pave the way for the intellectual revision of the western standpoint towards Islam, to open the door for a new understanding of Islam and the Muslims that goes beyond the complexities of the Crusades, the oriental discourse, and the colonial period. The findings of this study imply that the western scholars and opinion makers should develop their view of Islam and the Muslims on the basis of an in depth understanding of Islam based on the knowledge extracted from the genuine sources of Islam in a scientific manner.Keywords: Islamophobia, Orientalism, Islam, Conflict, Distortion